Manufacturing of dry electrodes for solid-state energy storage devices
A dry process for manufacturing all-solid-state batteries by coating and compressing a dry electrolyte powder on electrodes addresses the resistance issue, improving ion transfer and maintaining performance by avoiding solvent-related degradation.
Patent Information
- Application Number
- KR1020247011234
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-12
- Filing Date
- 2022-09-22
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-09-22
AI Technical Summary
Conventional all-solid-state battery assembly technologies result in a substantial boundary layer between the solid electrolyte and the electrode, hindering ion passage and increasing battery resistance, while electrolyte materials are sensitive to solvents used in wet coating methods, degrading battery performance.
A dry process is employed to manufacture electrodes by coating a dry electrolyte powder on an electrode film, followed by compression to form a solid electrolyte layer, using a shear force to fibrillate a binder and incorporating a dry electrolyte powder, which reduces the need for solvents like NMP and enhances ion transfer.
The method reduces battery resistance by facilitating easier ion passage through the electrode-electrolyte interface, maintaining battery performance without the degradation caused by solvent use in conventional methods.
Smart Images

Figure 112024037145392-PCT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention generally relates to a dry process for manufacturing energy storage devices, such as lithium-ion batteries, in particular for manufacturing all-solid-state batteries. Background Technology
[0002] This application is a continuation in part of U.S. Patent Application No. 17 / 492,458 "DRY ELECTRODE MANUFACTURE FOR SOLID STATE ENERGY STORAGE DEVICES" filed on October 1, 2021, the full disclosure of which is incorporated herein by reference.
[0003] There is significant interest in the development of all-solid-state batteries and other energy storage devices to address safety concerns regarding the use of flammable liquid electrolytes in lithium-ion batteries and other energy storage devices, as well as to utilize the high energy density achievable using lithium metal cathodes. In all-solid-state batteries, conventional liquid electrolytes and separators are replaced with ceramic or solid polymer electrolytes. Unfortunately, electrolyte materials tend to be sensitive to N-Methylpyrrolidone (NMP) or other solvents used to form solid electrolyte membranes using wet coating methods, which tends to degrade battery performance. Furthermore, current all-solid-state battery assembly technologies result in a substantial boundary layer between the solid electrolyte and the electrode, making it difficult for electrolyte ions to pass through and increasing battery resistance. As prior art related to this application, Chinese Patent Publication CN112133921 (December 25, 2020) is disclosed. The problem to be solved
[0004] The present invention considers various methods and devices to overcome the aforementioned disadvantages associated with the related technology. means of solving the problem
[0005] One aspect of an embodiment of the present invention is a method for manufacturing an electrode block for an all-solid-state battery. The method may include the steps of providing an electrode film having a current collector on a first surface of the electrode film, coating a dry electrolyte powder layer on a second surface of the electrode film opposite to the first surface, and compressing the dry electrolyte powder coated on the electrode film to produce a solid electrolyte layer on the electrode film.
[0006] The step of providing the current collector to the electrode film may include: preparing a powder mixture comprising at least one type of electrode active material and at least one type of fibrillable binder; applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder in the powder mixture; pressing the powder mixture into a free-standing film; and laminating the free-standing film onto the current collector. The powder mixture may further include at least one type of dry electrolyte powder.
[0007] Another aspect of an embodiment of the present invention is a method for manufacturing an all-solid-state battery. The method may include the steps of: providing a first electrode film having a first surface and a second surface opposite to the first surface; providing a second electrode film having a first surface and a second surface opposite to the first surface; coating the second surface of the first electrode film with a dry electrolyte powder layer; placing the second surface of the second electrode film on the dry electrolyte powder layer; and compressing the first electrode film coated with the dry electrolyte powder layer together with the second electrode film to manufacture an all-solid-state battery comprising the first electrode film, the second electrode film, and a solid electrolyte layer between them.
[0008] Any one or both of the steps of providing the first electrode film and providing the second electrode film may include the step of preparing a powder mixture comprising at least one type of electrode active material and at least one type of fibrillable binder, the step of applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder in the powder mixture, and the step of pressing the powder mixture into a self-supporting film. The powder mixture may further include at least one type of dry electrolyte powder.
[0009] The above method may include the step of laminating the first electrode film onto the first current collector while the first current collector is on the first surface of the first electrode film, and the step of laminating the second electrode film onto the second current collector while the second current collector is on the first surface of the second electrode film. The step of laminating the first electrode film and the step of laminating the second electrode film may be performed before coating or after compression.
[0010] Another aspect of an embodiment of the present invention is a method for manufacturing an electrode film for an all-solid-state battery. The method may include the steps of: preparing a powder mixture comprising at least one type of electrode active material, at least one type of fibrillable binder, and at least one type of dry electrolyte powder; wherein the at least one type of dry electrolyte powder is 5% to 30% by weight of the powder mixture, and applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder within the powder mixture; and compressing the powder mixture into a self-supporting film.
[0011] The above method may include the step of adding a solvent to the powder mixture to activate at least one type of fibrillable binder before fibrillation.
[0012] The above method may include the step of heating the powder mixture to 70°C or higher to activate at least one type of fibrillable binder before fibrillation.
[0013] The above powder mixture may include an additive solution comprising a polymer additive and a liquid carrier, and the additive solution is less than 5% by weight of the powder mixture.
[0014] The above powder mixture may include a conductive paste comprising a polymer additive, a liquid carrier, and a conductive material, and the conductive paste is less than 5 weight percent of the powder mixture.
[0015] Another aspect of an embodiment of the present invention is a self-supporting electrode membrane. The self-supporting electrode membrane may comprise at least one type of electrode active material, at least one type of fibrillable binder, and at least one type of dry electrolyte powder, wherein the dry electrolyte powder is 5% to 30% by weight of the self-supporting electrode membrane.
[0016] Another aspect of an embodiment of the present invention is a method for manufacturing an electrolyte membrane for an all-solid-state battery. The method may include the steps of: preparing a powder mixture comprising at least one type of fibrillable binder and at least one type of dry electrolyte powder; having at least one type of dry electrolyte powder constitute most of the powder mixture (e.g., 80% by weight or more of the powder mixture, e.g., 80% to 97% by weight or 80% to 99% by weight, preferably 95% to 99% by weight); applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder within the powder mixture; and compressing the powder mixture into a self-supporting membrane.
[0017] The above method may include the step of adding a solvent to a powder mixture to activate at least one type of fibrillable binder before fibrillation.
[0018] The above method may include the step of heating the powder mixture to 70°C or higher to activate at least one type of fibrillable binder before fibrillation.
[0019] The above powder mixture may include an additive solution comprising a polymer additive and a liquid carrier, and the additive solution is less than 5 weight percent of the powder mixture.
[0020] Another aspect of an embodiment of the present invention is a method for manufacturing an electrode block for an all-solid-state battery. The method may include the steps of performing the electrolyte membrane manufacturing method, providing an electrode membrane (with or without a current collector), and laminating a self-supporting electrolyte membrane on the electrode membrane.
[0021] Another aspect of an embodiment of the present invention is a self-supporting electrolyte membrane. The self-supporting electrolyte membrane may comprise at least one type of fibrillable binder and at least one type of dry electrolyte powder. The at least one type of dry electrolyte powder may constitute the majority of the self-supporting electrolyte membrane. For example, the dry electrolyte powder may be 80% by weight or more of the self-supporting electrolyte membrane, for example, 80% to 97% by weight or 80% to 99% by weight, preferably 95% to 99% by weight.
[0022] Another aspect of an embodiment of the present invention is a method for manufacturing an electrode block for an all-solid-state battery. The method may include the step of laminating the self-supporting electrolyte membrane onto the electrode membrane. Brief explanation of the drawing
[0023] The features and advantages of the various embodiments disclosed in this specification will be better understood by reference to the following description and drawings, and in the drawings, like numbers refer to the same parts as a whole. Figure 1 is a drawing illustrating a manufacturing apparatus for an electrode block for an all-solid-state battery. FIG. 1A is an enlarged view of the electrode block; FIG. 2 is a drawing illustrating an all-solid-state battery manufacturing apparatus; FIG. 2A is an enlarged view of an all-solid-state battery; FIG. 3 is a flowchart of the operation for manufacturing an electrode block; FIG. 4 is an operation flowchart for manufacturing an all-solid-state battery; FIG. 5 is an operation flow for manufacturing an electrode film, and is an exemplary sub-operation flow of step 310 of FIG. 3, step 410 of FIG. 4, or step 420 of FIG. 4. Figure 6 is a flowchart of operations for manufacturing an electrolyte membrane. Specific details for implementing the invention
[0024] The present invention includes various embodiments of all-solid-state batteries and electrodes, as well as methods for manufacturing and intermediate products thereof. The detailed description below, in conjunction with the accompanying drawings, is intended to describe various embodiments currently under consideration and is not intended to represent the only form in which the disclosed invention may be developed or utilized. The above description describes the functions and features associated with the exemplified embodiments. However, it should be understood that the same or equivalent functions may be achieved by other embodiments intended to be included within the scope of the present invention. Furthermore, the use of relational terms such as "first," "second," etc., is understood to be used merely to distinguish one entity from another, without necessarily requiring or implying an actual relationship or order between such entities.
[0025] FIG. 1 illustrates an apparatus (10) for manufacturing an electrode block (100) for an all-solid-state battery. FIG. 1A is an enlarged view of the electrode block (100), wherein the electrode block (100) may include an electrode film (110) and a solid electrolyte layer (120) stacked on the electrode film (110). Additional electrode blocks (100) may be stacked and / or wound to manufacture a multilayer battery, such as a cylindrical or prismatic cell. As described above, the device (10) may include one or more roll-to-roll processing devices, for example, a first spool (12) on which the electrode film (110) can initially be wound onto a roll, a second spool (14) on which a finished electrode block (100) can be wound, and one or more rollers (e.g., drive and / or idler rollers) for transferring the electrode film (110) from the first spool (12) to the second spool (14) through the device (10). Unlike conventional all-solid-state battery manufacturing apparatus, the apparatus (10) of FIG. 1 may include a scatter coater (11) or other means for coating a layer of dry electrolyte powder (119) on one side (114) of the electrode film (110), and subsequently the dry electrolyte powder (119) may be compressed by a roller press or calender (18) to produce a solid electrolyte layer (120) on the electrode film (110). In this way, the solid electrolyte layer (120) can be formed by a dry process while avoiding a significant amount of NMP or other solvent used in conventional slurry-based processes that can degrade the performance of the solid electrolyte. In addition, since the solid electrolyte layer (120) is formed directly on the electrode film (110) without subsequently being deposited on the electrode film (110), electrolyte ions can pass more easily through the interface between the electrode film (110) and the solid electrolyte layer (120), thereby reducing the battery resistance.
[0026] The electrode film (110) may be an anode film or a cathode film and may include an active material layer suitable for the anode or cathode, respectively. To assemble a multilayer battery, an electrode block (100) having anode and cathode electrode films (110) may be alternately stacked such that a solid electrolyte layer (120) separates each anode from an adjacent cathode and separates each cathode from an adjacent anode. For convenience of explanation, the electrode film (110) is exemplified as having only a single layer, i.e., an active material layer (e.g., may be 50 μm to 350 μm), and a dry electrolyte powder (119) is coated on one side (114). However, a current collector (e.g., may be 8 μm to 30 μm), such as an aluminum metal plate for the anode electrode film (110) or a copper metal plate for the cathode electrode film (110), may be stacked on the opposite side (112). Although not separately illustrated, such a current collector may exist for the process illustrated in FIG. 1 and may not only help provide stability while the dry electrolyte powder (119) is compressed into the solid electrolyte layer (120), but may also exist within the finished electrode block (100) illustrated in FIG. 1A. Additionally, although generally less practical, it may be considered that the current collector may be laminated onto the electrode block (100) after processing rather than before processing in FIG. 1.
[0027] FIG. 2 illustrates an apparatus (20) for manufacturing an all-solid-state battery (200). FIG. 2A is an enlarged view of an all-solid-state battery (200) comprising, in order, a first electrode film (210), a solid electrolyte layer (220), and a second electrode film (230) as illustrated. The apparatus (20) may be largely identical to the apparatus (10) of FIG. 1 and, similarly, may include a first spool (12) on which the first electrode film (210) may be initially wound onto a roll, a second spool (14) on which the all-solid-state battery (200) is wound, one or more rollers (16), a roller press or calender (18), and a scatter coater (11) or other means. The apparatus (20) may differ from the apparatus (10) in that a third spool (22) on which the second electrode film (230) is initially wound onto a roll is added. In the above device (20), the scatter coater (11) can coat a layer of dry electrolyte powder (119) on one side (214) of the first electrode film (210), and then one side (234) of the second electrode film (230) can be placed on the layer of dry electrolyte powder (119). Afterwards, the first electrode film (210) coated with the layer of dry electrolyte powder (119) can be compressed together with the second electrode film (230) using the roller press or calender (18) to manufacture an all-solid-state battery (200) comprising the first electrode film (210), the second electrode film (230), and the solid electrolyte layer (220) between them.
[0028] The device (10) illustrated in FIG. 1 and FIG. 1A can produce individual electrode blocks (100) for use in a multilayer battery, whereas the device (20) in FIG. 2 and FIG. 2A can produce a finished single-layer all-solid-state battery (200) having only one negative electrode and one positive electrode. Such a single-layer all-solid-state battery (200) can be packaged, for example, as a pouch cell or a button cell. It should be noted that either the first electrode layer (210) and the second electrode layer (230) may be a negative electrode and the other a positive electrode. That is, the dry electrolyte powder (119) may be coated on either the positive electrode or the negative electrode, then sandwiched by the other, and compressed to form the solid electrolyte layer (220).
[0029] Again, for convenience of explanation, the first electrode film (210) is exemplified as having only a single layer, i.e., an active material layer, with the dry electrolyte powder (119) coated on one side (214). Similarly, the second electrode film (230) is exemplified as having only an active material layer, with one side (234) disposed on the dry electrolyte powder (119). As such, it should be understood that a current collector, such as an aluminum metal plate for the positive electrode film (210, 230) or a copper metal plate for the negative electrode film (210, 230), may be laminated on the opposite side (212, 232), and that the current collector may be present in the process illustrated in FIG. 2 and in the finished all-solid-state battery (200) illustrated in FIG. 2A. However, since some single-cell batteries (200) may not have a current collector, such as coin cells that utilize the metal of the case for this purpose, the process of FIG. 2 can be realistically carried out without a current collector on the electrode film (210, 230). In this regard, since the additional electrode film (230) can introduce some degree of safety during compression compared to the process of FIG. 1, the process of FIG. 2 may have less practical need for metal current collector layer(s). Therefore, when a current collector is used in the finished all-solid-state battery (200), the electrode film (210, 230) can be laminated on each current collector before (and thus before compression) or after compression with the dry electrolyte powder (119).
[0030] FIG. 3 is a flow of operation for manufacturing an electrode block such as the electrode block (100) illustrated in FIG. 1A. The flow of operation may begin by providing an electrode film (110) that can generally be laminated onto a current collector as previously described (step 310). The electrode film (110) may be manufactured by any method including, for example, a slurry coating method, an extrusion method, and a dry method. Preferably, any dry method described in the inventor’s own prior patents and patent applications may be used, including U.S. Patent No. 10,069,131 titled “Electrode for Energy Storage Devices and Method of Making Same,” U.S. Patent Publication No. 2020 / 0388822 titled “Dry Electrode Manufacture by Temperature Activation Method,” U.S. Patent Application No. 17 / 014,862 titled “Dry Electrode Manufacture with Lubricated Active Material Mixture,” and U.S. Patent Application No. 17 / 097,200 titled “Dry Electrode Manufacture with Composite Binde,” each of which is incorporated whole by reference in this specification.
[0031] In particular, as described in more detail below, the electrode film (110) can be manufactured by preparing a powder mixture comprising at least one type of electrode active material (e.g., lithium metal oxide in the case of a positive electrode or graphite in the case of a negative electrode) and at least one type of fibrillable binder such as polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), or carboxymethylcellulose (CMC), applying a shear force to the powder mixture to fibrillate the binder, and compressing the powder mixture into a self-supporting film that can be laminated onto a current collector.
[0032] When the electrode film (110) is manufactured or otherwise provided, preferably when the electrode film (110) including a current collector on the first surface (112) is manufactured, the operation flow of FIG. 3 may continue to coat a layer of dry electrolyte powder (119) on the second surface (114) of the electrode film (110) opposite to the first surface (112) (step 320). As illustrated in FIG. 1, the coating of dry electrolyte powder (119) on the electrode film (110) may be part of a roll-roll process in which a scatter coater (11) coats the dry electrolyte powder (119) on the electrode film (110) when the electrode film (110) is transferred from the first spool (12) to the second spool (14) by one or more rollers (16), as illustrated in the apparatus (10). The above operation flow can be concluded by compressing the dry electrolyte powder (119) coated on the electrode film (110) to create a solid electrolyte layer (120) on the electrode film (110) (step 330). For example, as shown in FIG. 1, a roller press or calender (18) may compress the dry electrolyte powder (119) on the electrode film (110) to produce a solid electrolyte layer (120) as the dry electrode film (110) passes through the device (10) from the first spool (12) to the second spool (14). As described above, the finished electrode block (100) that can be used to manufacture a multilayer battery may be as shown in FIG. 1A (the current collector is omitted for convenience of explanation).
[0033] FIG. 4 is a flow of operation for manufacturing an all-solid-state battery such as the all-solid-state battery (200) illustrated in FIG. 2A. The flow of operation may begin with providing the first electrode film (210) and the second electrode film (230) (steps 410 and 420). As with the electrode film (110) described above, the electrode films (210, 230) may be manufactured by any method including a slurry coating method, an extrusion method, and a drying method, and may include, for example, any method among the methods described in the inventor's prior patents and patent applications incorporated by reference above. In particular, as described in more detail below, each electrode film (210, 230) can be manufactured by preparing a powder mixture comprising at least one type of electrode active material (e.g., lithium metal oxide in the case of a positive electrode or graphite in the case of a negative electrode) and at least one type of fibrillable binder (e.g., PTFE, PVP, PVDF, PEO, or CMC), applying a shear force to the powder mixture to fibrillate the binder, and compressing the powder mixture into a self-supporting film that can be laminated on the current collector. If the first electrode film (210) is manufactured as a positive active material, the second electrode film (230) can be manufactured as a negative active material. If the first electrode film (210) is manufactured as a negative active material, the second electrode film (230) can be manufactured as a positive active material.
[0034] If the electrode film (210, 230) is manufactured or otherwise provided and optionally includes a current collector on each of the first surfaces (212, 232), the operation flow of FIG. 4 may continue to coat a layer of dry electrolyte powder (119) on the second surface (214) of the first electrode film (210) opposite to the first surface (212) (step 430). As illustrated in FIG. 2, the coating of dry electrolyte powder (119) on the first electrode film (210) may be part of a roll-roll process in which a scatter coater (11) coats the dry electrolyte powder (119) on the first electrode film (110) as the first electrode film (110) is transferred from a first spool (12) to a second spool (14) by one or more rollers (16), as exemplified by the device (20). (The electrode film may be an anode or a cathode.) After the dry electrolyte powder (119) is coated on the first electrode film (210), the operation flow may continue to place a second electrode film (230) on the layer of dry electrolyte powder (119). In particular, the second surface of the second electrode film (230) (i.e., the opposite surface of the first surface (232) having an optional current collector) may be brought near the layer of dry electrolyte powder (119) as shown in FIG. 2 so that the first electrode film (210) and the second electrode film (230) are sandwiched with a layer of dry electrolyte powder (119). The operation flow may continue to manufacture an all-solid-state battery (200) comprising the first electrode film (210), the second electrode film (230), and a solid electrolyte layer (220) between them by compressing the first electrode film (210) coated with the layer of dry electrolyte powder (119) together with the second electrode film (230) (e.g., using a roller press or a calender (18)) (step 450). The completed all-solid-state battery (200) may be a single-layer battery as described above, and may be as shown in FIG. 2A.
[0035] The operation flow of FIG. 4 may be completed by laminating the first electrode film (210) onto a first current collector (e.g., an aluminum metal plate for the positive electrode or a copper metal plate for the negative electrode) and, likewise, laminating the second electrode film (230) onto a second current collector (steps 460, 470). These steps may follow step 450 as shown in FIG. 4, and the completed all-solid-state battery (200) is then laminated onto each current collector on both outer surfaces (212, 232). Alternatively, one or both of steps 460 and 470 may precede step 430, so that the electrode films (210, 230) are laminated onto each current collector before being coated with the dry electrolyte powder (119) as described above. In this case, FIG. 2A exemplifies the omission of these optional current collectors. Alternatively, steps 460 and 470 may both be omitted, which may be useful when manufacturing a specific button cell that does not use a current collector.
[0036] The dry electrolyte powder (119) used in one of the operation flows of FIGS. 3 and 4 (and by one of the devices (10, 20)) is mainly (e.g., 80 wt% to 100 wt%) a garnet-structure oxide, for example, various dopants (e.g., Li 6.5 La3Zr2O 12 or Li7La3Zr2O 12 Lithium lanthanum zirconium oxide (LLZO) and lithium lanthanum zirconium tantalum oxide (LLZTO), including ) (e.g., Li 6.4 La3Z 1.4 Ta 0.6 O 12 ), lithium lanthanum zirconium niobium oxide (LLZNbO) (e.g., Li 6.5 La3Zr 1.5 Nb 0.5 O 12 ), lithium lanthanum zirconium tungsten oxide (LLZWO) (e.g., Li 6.3 La3Zr 1.65 W0.35 O 12 ), perovskite structure oxides, e.g., lithium lanthanum titanate (LLTO) (e.g., Li 0.5 La 0.5 TiO3, Li 0.34 La 0.56 TiO3, or Li 0.29 La 0.57 TiO3) or lithium aluminum titanium phosphate (LATP) (e.g., Li 1.4 Al 0.4 Ti 1.6 (PO4)3), lithium superion conductor Li 2+2x Zn 1-x GeO4 (LISICON), for example, lithium aluminum titanium phosphate (LATP) (e.g., Li 1.3 Al 0.3 Ti 1.7 (PO4)3), lithium aluminum germanium phosphate (LAG or sodium superionic conductor, i.e., NASICON type LAGP) (e.g., Li 1.5 Al 0.5 Ge 1.5 (PO4)3 or Li 1.5 Al 0.5 Ge 1.5 P3O 12 ), or phosphates, e.g., lithium titanium phosphate (LTPO) (e.g., LiTi2(PO4)3), lithium germanium phosphate (LGPO) (e.g., LiGe2(PO4)3), lithium phosphate (LPO) (e.g., gamma-Li3PO4 or Li7P3O 11It may be a ceramic such as ) or lithium phosphate nitride (LiPON). As another example, the dry electrolyte powder (119) may be mainly (e.g., 80 wt% to 100 wt%) a polymer such as PEO, PEO-PTFE, PEO-LiTFSi, PEO-LiTFSi / LLZO, PEO-LiClO4, PEO-LiClO4 / LLZO, poly(3,4-ethylenedioxythiophene), polystyrene sulfonate (PEDOT:PSS), polyphenylene oxide (PPO), polyethylene glycol (PEG), polyether-based polymer, polyester-based polymer, nitrile-based polymer, polysiloxane-based polymer, polyurethane, poly-(bis((methoxyethoxy)ethoxy)phosphazene)(MEEP) or polyvinyl alcohol (PVA). As another example, the dry electrolyte powder (119) mainly (e.g., 80 wt% to 100 wt%) lithium sulfide (LS) (e.g., Li2S), glassy lithium phosphorus sulfide (LSPS) (e.g., Li2S-P2S5), glassy lithium boron sulfide (LSBS) (e.g., Li2S-B2S3), glassy lithium silicon sulfide (LSSiS) (e.g., Li2S-SiS2), lithium germanium sulfide (LGS) (e.g., Li4GeS4), lithium phosphorus sulfide (LPS) (e.g., Li3PS4 such as 75Li2S-25P2S5 or Li7P3S such as 70Li2S-30P2S5). 11 ), lithium silicon phosphate tin sulfide (LSPTS) (e.g., Li x (SiSn)P y S z ), Argyrodite Li6PS5X (X = Cl, Br) (e.g., LPSBr such as Li6PS5Br, LPSCl such as Li6PS5Cl, Li6PS5Cl 0.5 Br 0.5 LPSClBr or Li such as 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3LSiPSCl) or thio-LISICON (e.g., Li 10 GePS 12 It can be a sulfide such as LGPS).
[0037] FIG. 5 is an operation flow for manufacturing electrode films such as the electrode films (110, 210, 230) described above. Accordingly, FIG. 5 may be an example of a sub-operation flow of step 310 of FIG. 3, step 410 of FIG. 4, or step 420 of FIG. 4. In particular, FIG. 5 provides an example of a dry method for manufacturing positive or negative electrode films (110, 210, 230), which can be used to manufacture an electrode block (100) of a multilayer battery according to the operation flow of FIG. 3 or to manufacture a single-layer battery according to the operation flow of FIG. 4. As described above, the manufacture of electrode films (110, 210, 230) by a dry method may generally include the steps of preparing a powder mixture comprising at least one type of electrode active material and at least one type of fibrillable binder, applying a shear force to the powder mixture to fibrillate the binder, and compressing the powder mixture into a self-supporting film that can be laminated on a current collector. More specifically, the operation flow of FIG. 5 may begin with preparing a powder mixture for the electrode films (110, 210, 230) (step 510). The electrode active material may constitute most of the powder mixture, for example, 82% to 99% by weight (e.g., 94% by weight) of the powder mixture. In the case of the positive electrode, the electrode active material may be a lithium metal oxide such as lithium manganese oxide (LMO), lithium nickel manganese cobalt oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese oxide (LMNO), etc. In the case of the cathode, the electrode active material may be graphite, silicon dioxide (SiO2), a mixture of the two, etc. Depending on the conductivity of the active material, for example, 0% to 10% by weight (e.g., 4% by weight) of a conductive material may be added to the powder mixture.The conductive material may include carbon black such as activated carbon, acetylene black, Kezen black, or Super P (e.g., carbon black sold under the trade name SUPER P® by Imerys Graphite & Carbon of Switzerland), carbon nanotubes (CNT), graphite particles, conductive polymers, or combinations thereof.
[0038] To form the electrode film (110, 210, 230) by a dry method (thus avoiding the long drying time associated with conventional slurry coating and extrusion methods), the powder mixture may further include at least one type of fibrillable binder such as polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), or carboxymethylcellulose (CMC), which includes a composite binder as described in U.S. Patent Application No. 17 / 097,200 titled “Dry Electrode Manufacture with Composite Binder” incorporated by reference above. The fibrillable binder may be characterized by a soft and flexible consistency, particularly elasticity such that it becomes longer and thinner and takes on a fibrous state when subjected to shear force. As described below, since one or more fibrillable binders that can be chemically or thermally activated to increase flexibility are used, the powder mixture can be compressed into a self-supporting membrane without breakage and without excessive use of solvents such as NMP.
[0039] As described in more detail in U.S. Patent Application No. 17 / 014,862, 'Dry Electrode Manufacture with Lubricated Active Material Mixture,' incorporated by reference above, the powder mixture containing the electrode active material may be lubricated by mixing it into a polymer-containing additive solution or a conductive paste before adding the binder. For example, the powder mixture may contain, in addition to the electrode active material (and in addition to the fibrillable binder to be added later), an additive solution containing a polymer additive and a liquid carrier. Since the additive solution may be less than 5 weight percent of the powder mixture, the powder mixture may remain a dry powder despite the relatively small amount of liquid added. For example, the final powder mixture containing the electrode active material, any conductive material, the fibrillable binder and additive solution, as well as any electrolyte powder (see below), may have a total solid content exceeding 95 weight percent. The polymer additive, which may be 0.5% to 10% by weight of the above additive solution, may be a polymer compound, surfactant, or high-viscosity liquid (e.g., mineral oil or wax) such as those known to be used as dispersants or binders for carbon nanotubes.
[0040] For example, U.S. Patent No. 8,540,902 provides examples of dispersants and polymeric binders comprising polyethylene, polypropylene, polyamide, polyurethane, polyvinyl chloride, polyvinylidene fluoride, thermoplastic polyester resin, polyvinylpyrrolidone, polystyrene sulfonate, polyphenylacetylene, polymeta-phenylenenevillene, polypyrrole, polyphenylene benzobisoxazole, natural polymers, amphiphilic substances in aqueous solutions, anionic aliphatic surfactants, sodium dodecyl sulfate, cyclic lipopeptido biosurfactants, water-soluble polymers, polyvinyl alcohol sodium dodecyl sulfate, polyoxyethylene surfactants, polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), hydroxyl ethyl cellulose polyacrylic acid, polyvinyl chloride, and combinations thereof. Another polymer additive may be styrene-butadiene rubber (SBR). The liquid carrier used to produce the additive solution may be aqueous or non-aqueous and may include, for example, one or more chemicals selected from the group consisting of n-methylpyrrolidone, hydrocarbons, acetate esters, alcohols, glycols, ethanol, methanol, isopropanol, acetone, diethyl carbonate, and dimethyl carbonate.
[0041] Alternatively, the powder mixture may comprise a conductive paste comprising a polymer additive, a liquid carrier, and a conductive material in addition to the electrode active material (and in addition to the fibrillable binder to be added later). As with the additive solution described above, the conductive paste may be less than 5 weight percent of the powder mixture. For example, the final powder mixture comprising the electrode active material, the fibrillable binder, and the conductive paste (generally, no separate conductive material is used in the powder mixture), as well as any electrolyte powder (see below), may have a total solid content exceeding 95 weight percent. The conductive paste may differ from the additive solution in that, for example, 1 weight percent to 20 weight percent, preferably 2 weight percent to 15 weight percent, more preferably 5 weight percent to 10 weight percent of the conductive paste is added as a conductive material. The conductive paste may be, for example, a CNT paste commonly used to enhance electrical conductivity in wet mixtures used in coating methods such as those exemplified in U.S. Patent No. 8,540,902. For example, the conductive paste may be composed of 3.08 wt% PVP as a polymer additive, 91.67 wt% NMP as a liquid carrier, and 6.25 wt% carbon nanotubes as a conductive material.
[0042] In order for the manufactured electrode film (110, 210, 230) to more easily exchange electrolyte ions with the solid electrolyte layer (120, 220) of the completed electrode block (100) or all-solid-state battery (200) to reduce battery resistance, the powder mixture may include at least one type of dry electrolyte powder. For example, the amount of dry electrolyte powder in the powder mixture may be 5% to 30% by weight. The dry electrolyte powder included in the powder mixture may be the same as or different from the dry electrolyte powder (119) used to form the solid electrolyte layer (120, 220), and may be, for example, any of the materials described above in relation to the dry electrolyte powder (119).
[0043] With a powder mixture prepared comprising the electrode active material, any additive solution or conductive paste for lubricating the electrode active material, a fibrillable binder, any additional conductive material, and preferably at least one type of dry electrolyte powder, the operation flow of FIG. 5 may continue to activate the fibrillable binder by one or more activation methods. In the solvent activation step, a solvent may be added to the powder mixture to chemically activate the fibrillable binder, which softens the fibrillable binder, allows it to be stretched longer and finer without breaking, and improves adhesive strength (step 520). Unlike solvents such as NMP, which are difficult to remove and may involve a long drying process, the solvent added in the solvent activation step (520) may have a relatively low boiling point of less than 130°C or less than 100°C (i.e., lower than the boiling point of water). For example, the solvent may include hydrocarbons (e.g., hexane, benzene, toluene), acetates (e.g., methyl acetate, ethyl acetate), alcohols (e.g., propanol, methanol, ethanol, isopropyl alcohol, butanol), glycols, acetone, dimethyl carbonate (DMC), diethyl carbamazine (DEC), tetrachloroethylene, etc. Unlike slurry coating and extrusion processes, where the solvent may be 60% to 80% by weight of the resulting wet mixture, the solvent added in step 520 may be less than 20% of the resulting mixture. For example, the ratio of the powder mixture to the added solvent may be about 100:10, 100:5, or 100:3.
[0044] Instead of or in addition to the solvent activation of step 520, the operation flow may include a temperature activation step (step 530) for thermally activating the fibrillable binder by heating the powder mixture to 70°C or higher, preferably 100°C or higher. Similar to the solvent activation step (step 520), the temperature activation step (step 530) can improve adhesive strength by softening the fibrillable binder and allowing it to be stretched longer and finer without breaking. In the temperature activation step (step 530), the temperature at which the powder mixture is heated may be lower than the glass transition temperature of the binder (e.g., 114.85°C for PTFE), as softening of the binder may occur before reaching the glass transition temperature. Alternatively, the mixture may be heated to a temperature above the glass transition temperature of the binder. When both the solvent activation step (520) and the temperature activation step (530) are used, the two steps can be performed in any order.
[0045] With the fibrillable binder chemically and / or thermally activated by one or both of steps 520 and 530, the flow of operation of FIG. 5 may continue to apply a shear force to the powder mixture to fibrillate the binder within the powder mixture (step 540). For example, the powder mixture may be mixed in a standard kitchen blender or an industrial blender. Appropriate shear force to deform (e.g., stretch) the fibrillable binder to create a stickier and more flexible mixture may be achieved by mixing the powder mixture in a blender at about 10,000 RPM for 1 to 10 minutes (e.g., 5 minutes), or by a mixing process using a commercial dough mixer or an industrial-sized mortar and pestle. Preferably, a high-shear mixer such as a high-shear granulator (e.g., a jet mill) may be used. If a solvent is added in the solvent activation step (step 520) to chemically activate the binder, the solvent may be injected into the powder mixture in some cases while the powder mixture is subjected to shear force in step 540. Thus, steps 520 and 540 can be performed in a single step.
[0046] After a shear force is applied to the mixture, the operation flow of FIG. 5 may continue to the step (550) of compressing the mixture to produce a self-supporting film that will serve as an electrode film (110, 210, 230). This may be performed, for example, using a roller press or a calender at a temperature of 150°C and a roll gap of 20 μm. The manufactured self-supporting electrode film (110, 210, 230) may contain at least one type of electrode active material, at least one type of fibrillable binder, and at least one type of dry electrolyte powder in an amount of 5% to 30% by weight of the self-supporting electrode film. When electrode films (110, 210, 230) are laminated onto a current collector before forming a solid electrolyte layer (120, 220) by coating a dry electrolyte powder (119) (steps 320, 430), the operation flow of FIG. 5 can be completed by laminating the self-supporting electrode films (110, 210, 230) onto the current collector (step 560). For example, as described above, this may be particularly advantageous when manufacturing an electrode block (100) for a multilayer battery according to the operation flow of FIG. 3 (i.e., when FIG. 5 is a sub-operation flow of step 310). If the current collector is not used or is added later (as in the case of optional steps 460 and 470 of FIG. 4), step 560 may be omitted.
[0047] As described above, the operation flow of FIG. 5 can be advantageously used to manufacture the electrode film(s) (110, 210, 230) illustrated in FIG. 1 and 2, and then can be assembled into an electrode block (100) of a multilayer all-solid-state battery according to the operation flow of FIG. 3 or assembled into a single-layer all-solid-state battery (200) according to the operation flow of FIG. 4. To this end, the powder mixture prepared in step 510 of FIG. 5 may preferably include at least some dry electrolyte powder as described above, which can make the activated dry process described herein uniquely suitable for manufacturing an all-solid-state battery. In this way, by combining the operation flow of FIG. 5 with the operation flow of FIG. 3 or FIG. 4 to manufacture the electrode block (100) or the all-solid-state battery (200) completely from start to finish using a dry method, the long drying time and degradation of battery performance associated with the conventional wet method can be completely avoided, thereby enabling the manufacturing of a more practical and efficient all-solid-state battery.
[0048] FIG. 6 is a flowchart of the operation for manufacturing an electrolyte membrane. The flowchart of FIG. 6 may be part of an alternative methodology for manufacturing a dry all-solid-state battery. Unlike the solid electrolyte layer (120, 220) described in relation to FIG. 1 to 4, which is formed from a dry electrolyte powder (119) directly coated on an electrode membrane (110, 210), the solid electrolyte layer manufactured in FIG. 6 is in the form of a self-supporting membrane that can subsequently be laminated onto the electrode membrane. In this regard, it should be noted that the electrode membrane to accommodate the electrolyte membrane of FIG. 6 can still be manufactured according to the dry method of FIG. 5, and thus another completely dry process for manufacturing an all-solid-state battery may occur.
[0049] The operation flow of FIG. 6 can be viewed as similar to a dry method for manufacturing an electrode film (e.g., the exemplary method of FIG. 5), but the main difference is that the powder mixture contains components for manufacturing a solid electrolyte rather than an anode or a cathode. In particular, the operation flow of FIG. 6 may begin with preparing a powder mixture for an electrolyte film (step 610). In this case, the dry electrolyte powder (not the electrode active material) may constitute most of the powder mixture, for example, 80 wt% or more, for example, 80 wt% to 97 wt% or 80 wt% to 99 wt%, preferably 95 wt% to 99 wt%. Examples of the dry electrolyte powder may include any of the materials listed above in relation to the dry electrode powder (119). To form the electrolyte membrane by a dry method (thus avoiding the long drying time associated with conventional wet methods), the powder mixture may further include at least one type of fibrillable binder, such as PTFE, PVP, PVDF, PEO, or CMC, comprising the composite binder described in U.S. Patent Application No. 17 / 097,200 “Dry Electrode Manufacture with Composite Binder” incorporated by reference above. As described above, using one or more fibrillable binders that can be chemically or thermally activated to increase flexibility allows the powder mixture to be compressed into a self-supporting membrane without breakage and without excessive use of solvents such as NMP.
[0050] As with the powder mixture for the electrode membrane (110, 210, 230) above, it is considered that the powder mixture containing the dry electrolyte powder can be lubricated by mixing a polymer-containing additive solution before adding the binder. For example, the powder mixture may contain an additive solution containing a polymer additive and a liquid carrier in addition to the dry electrolyte powder (and in addition to the fibrillable binder to be added later). Since the additive solution may be less than 5 weight percent of the powder mixture, the powder mixture may remain a dry powder despite the addition of a relatively small amount of liquid. For example, the final powder mixture containing the dry electrolyte powder, the fibrillable binder, and the additive solution may have a total solid content exceeding 95 weight percent. The polymer additive may be the same as that described above. The aforementioned conductive paste is generally not used when preparing the powder mixture for the electrode membrane because conductivity is not generally required in solid electrolytes.
[0051] With a powder mixture prepared comprising the dry electrolyte powder, any additive solution for lubricating the dry electrolyte powder, and a fibrillable binder, the operation flow of FIG. 6 may continue to activate the fibrillable binder by one or more activation methods. That is, the operation flow of FIG. 6 may include a solvent activation step (step 620) identical to the solvent activation step (step 520) of FIG. 5 and / or a temperature activation step (630) identical to the temperature activation step (step 530) of FIG. 5. In this way, the fibrillable binder is chemically and / or thermally activated so that it becomes soft and can be stretched longer and finer without breaking, thereby improving adhesive strength. If both the solvent activation step (step 620) and the temperature activation step (step 630) are used, the two steps may proceed in any order. The operation flow of FIG. 6 may continue by applying a shear force to the powder mixture, which may be identical to step 540 of FIG. 5, to fibrillate the binder within the powder mixture (step 640). If the binder is chemically activated by adding a solvent in the solvent activation step (step 620), the solvent may be injected into the powder mixture while the powder mixture is subjected to a shear force in step 640. Thus, steps 620 and 640 may be performed in a single step.
[0052] After the above mixture is subjected to shear force, the operation flow of FIG. 6 may be concluded with a step (step 650) of compressing the mixture to produce a self-supporting membrane, which may be performed in the same manner as, for example, the step (step 550) of FIG. 5. The resulting self-supporting electrolyte membrane may comprise at least one type of fibrillable binder and at least one type of dry electrolyte powder constituting most of the self-supporting electrolyte membrane, for example, 80 wt% or more, for example, 80 wt% to 97 wt% or 80 wt% to 99 wt%, preferably 95 wt% to 99 wt%. Such a self-supporting electrolyte membrane may then be laminated onto an electrode membrane (one of a positive or negative electrode) to produce an all-solid-state battery or an intermediate product thereof (e.g., an electrode block of a multilayer all-solid-state battery). Similar to the operation flow of FIG. 3 and FIG. 4, the operation flow of FIG. 6 can be used in conjunction with the operation flow of FIG. 5 to manufacture an all-solid-state electrode block or an all-solid-state battery using a completely dry method from start to finish. In this way, the long drying time and degradation of battery performance associated with conventional wet methods can be completely avoided, making it possible to manufacture a more practical and efficient all-solid-state battery.
[0053] The foregoing description is provided as an example and is not limited thereto. Taking the foregoing description into account, those skilled in the art may devise variations that fall within the scope and spirit of the present invention. Furthermore, the various features of the embodiments disclosed herein may be used alone or in various combinations with one another, and are not intended to be limited to the specific combinations described herein. Accordingly, the scope of the claims is not limited by the exemplified embodiments.
Claims
Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 A method for manufacturing an electrode film for an all-solid-state battery, comprising the steps of: preparing a powder mixture comprising at least one type of electrode active material, at least one type of fibrillable binder, and at least one type of dry electrolyte powder; adding a solvent to the powder mixture to activate at least one type of fibrillable binder, wherein the dry electrolyte powder is 5% to 30% by weight of the powder mixture; applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder within the powder mixture; and pressing the powder mixture into a self-supporting film. Claim 11 delete Claim 12 A method for manufacturing an electrode film for an all-solid-state battery according to claim 10, further comprising the step of heating the powder mixture to 70°C or higher to activate at least one type of fibrillable binder before the fibrillation step. Claim 13 A method for manufacturing an electrode film for an all-solid-state battery according to claim 10, wherein the powder mixture further comprises an additive solution containing a polymer additive or a liquid carrier, and the additive solution is less than 5% by weight of the powder mixture. Claim 14 A method for manufacturing an electrode film for an all-solid-state battery according to claim 10, wherein the powder mixture further comprises a conductive paste comprising a polymer additive, a liquid carrier, and a conductive material, and the conductive paste is less than 5% by weight of the powder mixture. Claim 15 A self-supporting electrode membrane comprising: at least one type of electrode active material; at least one type of fibrillable binder that is fibrillated after activating at least one type of fibrillable binder by adding one or more solvents; and at least one type of dry electrolyte powder, wherein the dry electrolyte powder is 5% to 30% by weight of the self-supporting electrode membrane. Claim 16 A method for manufacturing an electrolyte membrane for an all-solid-state battery, comprising the steps of: preparing a powder mixture comprising at least one type of fibrillable binder and at least one type of electrolyte powder; adding a solvent to the powder mixture to activate at least one type of fibrillable binder, wherein at least one type of dry electrolyte powder constitutes the majority of the powder mixture; applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder within the powder mixture; and compressing the powder mixture into a self-supporting electrolyte membrane. Claim 17 A method for manufacturing an electrolyte film for an all-solid-state battery, wherein, in claim 16, at least one type of dry electrolyte powder is 80% to 97% by weight of the powder mixture. Claim 18 A method for manufacturing an electrolyte membrane for an all-solid-state battery, wherein, in claim 16, at least one type of dry electrolyte powder is 80 weight percent or more of the powder mixture. Claim 19 A method for manufacturing an electrolyte film for an all-solid-state battery, wherein, in claim 18, at least one type of dry electrolyte powder is 80% to 99% by weight of the powder mixture. Claim 20 A method for manufacturing an electrolyte membrane for an all-solid-state battery, wherein, in claim 19, at least one type of dry electrolyte powder is 95% to 99% by weight of the powder mixture. Claim 21 delete Claim 22 A method for manufacturing an electrolyte membrane for an all-solid-state battery according to claim 16, further comprising the step of heating the powder mixture to 70°C or higher to activate at least one type of fibrillable binder before the fibrillation step. Claim 23 A method for manufacturing an electrolyte membrane for an all-solid-state battery according to claim 16, wherein the powder mixture further comprises an additive solution containing a polymer additive or a liquid carrier, and the additive solution is less than 5% by weight of the powder mixture. Claim 24 A method for manufacturing an electrode block for an all-solid-state battery, comprising the method of claim 16; the step of providing an electrode film having a current collector on a first surface of the electrode film; and the step of laminating a self-supporting electrolyte film on a second surface opposite to the first surface of the electrode film. Claim 25 In claim 24, the step of providing an electrode film having the current collector comprises: preparing a powder mixture comprising at least one type of electrode active material and at least one type of fibrillable binder; applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder in the powder mixture; pressing the powder mixture into a self-supporting film; and laminating the self-supporting film on the current collector. Claim 26 In claim 25, the above powder mixture further comprises at least one type of dry electrolyte powder. A method for manufacturing an electrode block for an all-solid-state battery. Claim 27 A method for manufacturing an electrode block for an all-solid-state battery, comprising the method of claim 16; the step of providing an electrode film; and the step of laminating a self-supporting electrolyte film on the electrode film. Claim 28 In claim 27, the step of providing the electrode film comprises: preparing a powder mixture comprising at least one type of electrode active material and at least one type of fibrillable binder; applying a shear force to the powder mixture to fibrillate at least one type of fibrillable binder in the powder mixture; and pressing the powder mixture into a self-supporting film, thereby manufacturing an electrode block for an all-solid-state battery. Claim 29 In claim 28, the method for manufacturing an electrode block for an all-solid-state battery further comprises at least one type of dry electrolyte powder in the powder mixture. Claim 30 A self-supporting electrolyte membrane comprising: at least one type of fibrillable binder that is fibrillated after activating at least one type of fibrillable binder by adding one or more solvents; and at least one type of dry electrolyte powder, wherein the dry electrolyte powder constitutes 80% to 97% by weight of the self-supporting electrolyte membrane. Claim 31 A self-supporting electrolyte membrane comprising: at least one type of fibrillable binder that is activated by adding one or more solvents and then fibrillated; and at least one type of dry electrolyte powder, wherein the at least one type of dry electrolyte powder is the majority of the self-supporting electrolyte membrane by weight. Claim 32 In claim 31, the above at least one type of dry electrolyte powder is a self-supporting electrolyte membrane comprising 80 weight percent or more of the above self-supporting electrolyte membrane. Claim 33 In claim 32, the above at least one type of dry electrolyte powder is a self-supporting electrolyte membrane comprising 80% to 99% by weight of the above self-supporting electrolyte membrane. Claim 34 In claim 33, the above at least one type of dry electrolyte powder is a self-supporting electrolyte membrane comprising 95% to 99% by weight of the above self-supporting electrolyte membrane. Claim 35 A method for manufacturing an electrode block for an all-solid-state battery, comprising the steps of: providing a self-supporting electrolyte membrane according to claim 31; and laminating the self-supporting electrolyte membrane on an electrode membrane.
Citation Information
Patent Citations
Electrolyte membrane, preparation method thereof and battery
CN111916633A
Positive electrode material layer suitable for all-solid-state battery, preparation method of positive electrode material layer, positive plate and all-solid-state battery
CN112133921A
Method of making a battery
US6368365B1
